Efektivitas Penggunaan Aplikasi Mommy Warning Terhadap Ketepatan Waktu Kunjungan Ulang Akseptor Kontrasepsi Suntik 1 Bulan Di PMB “RB” Tahun 2024 - Ramadhani, Puteri Ahyana; Rizani, Ahmad; Rafidah, Rafidah; Zakiah, Zakiah (JURNAL KEBIDANAN BESTARI, 2024)
Introduction: Cempaka Subdistrict was the subdistrict that had the highest dropout rate, with 661 people (18.9%) who accepted family planning. According to a previous study conducted by researchers at PMB "RB," secondary data revealed that the target for monthly injectable family planning visits at PMB "RB" from October 2023 to January 2024 was only achieved 80% of the time. Direct interviews with midwives indicated that 40- 45% of the acceptors followed through. Injectable contraceptives experienced inaccuracies in revisit times. Purpose: effectiveness in using the Mommy Warning Application for repeat visits among 1-month injection acceptors at PMB "RB" in 2024. Method: This research used a pre-experimental method with a one-group pre- post test design. The sample included all acceptors selected through total sampling. The independent variable was the Mommy Warning re-visit reminder application, and the dependent variable was the revisit for 1-month injections. Data collection involved filling out a Google form to gather identity information, history of return visits, and observations through the register book. Data were analyzed using the Wilcoxon test with a p-value of 0.02. Results: The results showed effectiveness in using the Mommy Warning Application for repeat visits among 1-month injection acceptors at PMB "RB" in 2024. Conclusion: Therefore, it is highly recommended for all acceptors to utilize the Mommy Warning Application to reduce revisit inaccuracies for 1-month injections.Keywords: Application Effectiveness, Visit Timeliness, 1-Month Injectable Contraceptives